Assertive Speech Acts in Mata Najwa Program of Episode Gare-Gare Corona (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
The main objective of this study is to find out the types and functions of assertive speech acts that appear in Mata Najwa program in episode Gara-Gara Corona. The method used in this study is a qualitative descriptive method by analyzing and explaining the data obtained. The data in this study were speech segments in the Mata Najwa episode Gara-Gara Corona which indicate assertive speech acts. The data source in this study is the video of the program entitled "gara-gara Corona" taken from Youtube, which was published by Narration Newsroom on March 13, 2020. The steps taken in data collection techniques were, firstly downloading video from Youtube, the second listens to the utterances, and the third transcribes the utterances into written language. Then the speech data obtained was selected based on research questions related to the types and functions of assertive speech acts. At the stage of presenting the results of the analysis, it was presented using an informal presentation method, namely presentation using ordinary words. The results showed that the assertive speech act types that appeared in the event were 23 pairs of utterances, consisting of 11 pairs of assertive speech acts telling, 6 pairs of assertive speech acts stated, 3 pairs of assertive speech acts suggest, and 3 pairs of utterances assertive speech acts boast.